The Ecologic Validity of Fructose Feeding Trials: Supraphysiological Feeding of Fructose in Human Trials Requires Careful Consideration When Drawing Conclusions on Cardiometabolic Risk - Choo, Vivian L.; Sievenpiper, John L. (Frontiers in Nutrition, 2015)
Background Select trials of fructose overfeeding have been used to implicate fructose as a driver of cardiometabolic risk. Objective We examined temporal trends of fructose dose in human controlled feeding trials of fructose and cardiometabolic risk. Methods We combined studies from eight meta-analyses on fructose and cardiometabolic risk to assess the average fructose dose used in these trials. Two types of trials were identified: (1) substitution trials, in which energy from fructose was exchanged with equal energy from other carbohydrates and (2) addition trials, in which energy from fructose supplemented a diet compared to the diet alone. Results We included 64 substitution trials and 16 addition trials. The weighted average fructose dose in substitution trials was 101.7 g/day (95% CI: 98.4–105.1 g/day), and the weighted average fructose dose in addition trials was 187.3 g/day (95% CI: 181.4–192.9 g/day). Conclusion Average fructose dose in substitution and addition trials greatly exceed national levels of reported fructose intake (49 ± 1.0 g/day) (NHANES 1977–2004). Future trials using fructose doses at real world levels are needed.